Management issues in hypertensive diabetics - James A. Ker (South African Family Practice)
This article discusses seven issues in the management of hypertension in diabetic patients, namely the importance of blood pressure control, optimal blood pressure control levels, the importance of blocking the renin-angiotensin system, the inevi-tability of combination anti-hypertensive therapy, drug choices, the diabetogenic effects of high dose thiazide diuretics and beta-blockers and the importance of treating other risk factors, like dyslipidaemia.